Factors contributing to sepsis among adult patients in the surgical unit at China-Uganda Friendship Hospital, Naguru, Kampala district. A cross-sectional study. - Nabbuga, Mariam; Nansereko, Hasifa; Nalubega, Jane Frank; Naggulu Posperia, Immaculate; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David (Student's Journal of Health Research Africa, 2025)
Background In Uganda, sepsis remains a significant cause of morbidity and mortality among hospitalized patients, particularly in surgical wards. The purpose of this study was to determine the factors contributing to sepsis among adult patients in the surgical unit at China-Uganda Friendship Hospital, Naguru, Kampala District. Methods A descriptive cross-sectional study design employing a quantitative research method was used to obtain data. In four days, 44 adult patients were sampled by a simple random sampling technique using a structured questionnaire, and data were analyzed using Microsoft Office (2013) version, and the results were presented in the form of tables, graphs, and pie charts. Results out of 44 study respondents sampled, more than half (52.3%) were aged between 26 and 32 years, and 36.4% had attained secondary school education. Regarding the individual-related factors, more than half (59.1%) reported that post-surgical care was expensive, more than half (54.5%) had long-term illness, (40.9%) frequently used traditional medicine, and most (70.5%) rated their post-surgical nutrition as poor. Pertaining to health facility-related factors, a significant (86.4%) reported that necessary medicines and supplies for wound care were rarely available, and more than half (54.5%) found healthcare workers to be rude during follow-up visits. Conclusion Sepsis in adult patients was influenced by both personal factors and healthcare facility-related issues. Many adults faced challenges such as unaffordable post-surgical care and pre-existing chronic conditions, which hindered wound healing and heightened their risk of infections. Recommendation There is a need to establish subsidized post-operative care packages, especially for patients with chronic illnesses like diabetes and hypertension, to reduce the financial burden and improve recovery outcomes.